An Experience with Misoprostol for the Induction of First Trimester Abortions in a Secondary Hospital in South Africa - J. Fuchs; H. de Klerk; P.J.T. de Villiers; C. Atzl (South African Family Practice)
Background: Misoprostol is a prostaglandin analogue with uterotonic properties. Administered orally or vaginally, it is an effective agent for induction of first trimester abortions. Aim: To establish the effectiveness and complications arising within the first week following the administration of Misoprostol for termination of pregnancy (TOP) in the first trimester of pregnancy. Setting: A regional hospital in the Helderberg basin of the greater Cape Town area, serving both as district and secondary hospital. Methods: Prospective descriptive study of patients using Misoprostol as induction agent in the first trimester of pregnancy. Success rate, side effects and complications were monitored over three visits, up until one week after termination Results: 105 patients were enrolled into the study. Following the intake of Misoprostol, 70% reported a successful induction within 48 hours. The evacuation of the uterus was found to be uncomplicated in 64% of these patients. 9% received a repeat dose of Misoprostol, 3% required a third medical induction. In 1 patient with an unsuccessful induction, an ectopic pregnancy was diagnosed. In 4 women the uterus had been surgically perforated, without need for further surgery. Conclusion: The use of Misoprostol for the induction of termination of pregnancy in the first trimester proved to be effective and acceptably safe.